Forms, Methods, and Tools of Using the Scientific Heritage of Central Asian Scientists in the Process of Higher Pedagogical Education - Muradov Farhodjon Murodjon o’g’li (Researchparks Publishing, 2023)
We know that the science of mathematics develops a person's intelligence, attention, develops determination and will, algorithmic order provides discipline and expands thinking. In this article, we describe the use of forms, methods, and tools in organizing educational activities for students based on the rich scientific heritage of Eastern scholars.